Organizational Leadership through the Massive Transformative Purpose - Kiril Dimitrov (Economic Alternatives, 2022)
Purpose: This study aims at justifying the affiliation of the massive transformative purpose as an important item in the aggregate of the proclaimed corporate culture elements. For this reason the bundle of shades in the meaning for the massive transformative purpose will be explored, bearing in mind the main researcher's interest in outlining the cultural facet of the construct the attributes of which should be further categorized as official and unofficial ones. Methodology: Literature review and critical analysis of academic publications and blogs of business leaders and consultants in the sphere of the exponential organizations are performed in order to identify important shades in the meaning of the massive transformative purpose. The latter are summarized and categorized as basic nuances and new elaboration streams by the application of the mind-map method. Secondary data analysis and an ethnographic research method are used to identify the cultural facets of the construct, based on its shades of meaning. Findings: A set of interconnected nuances in the meaning of the massive transformative purpose is grounded through the performed review and critical analysis of books, scientific articles and blogs. The aforementioned nuances are logically and hierarchically arranged by two useful mind-maps. The outlined cultural facet of the massive transformative purpose is structured into two parts: (1) the first one, containing the core shades of meaning of the construct, and (2) the second one, encompassing the identified new elaboration streams for the construct. Thus, it became possible to propose two new definitions for the massive transformative purpose, embodying the aforementioned parts. In this way, the massive transformative purpose is directly determined as an element of the proclaimed corporate culture, used to formulate and communicate officially the leadership intents of future business development.
Keywords: L21; M13; M14; 330; massive transformative purpose; MTP; corporate culture; proclaimed corporate culture; organizational leadership; strategic management; exponential organizations; startups